Optimization of Hospital Health Services: Insights from Recent Literature - Parindra, I Ketut; Menap, Menap; Khalik, Lalu Abdul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The objective of this study is to conduct a comprehensive literature review to identify and analyze strategies for optimizing hospital health services within the last year. Utilizing the PRISMA methodology, the study systematically reviewed articles from the SCOPUS database using the keyword